Intuitive eating ebook A revolutionary anti-diet approach. - Tribole, Evelyn, M.S, R.D (St. Martin's Essentials, 2020)
Make peace with food. Free yourself from chronic dieting forever. Rediscover the pleasures of eating. The go-to resource––now fully revised and updated––for building a healthy body image and making peace with food, once and for all. When it was first published, Intuitive Eating was revolutionary in its anti-dieting approach. The authors, both prominent health professionals in the field of nutrition and eating disorders, urge readers to embrace the goal of developing body positivity and reconnecting with one's internal wisdom about eating—to unlearn everything they were taught about calorie-counting and other aspects of diet culture and to learn about the harm of weight stigma. Today, their message is more relevant and pressing than ever. With this updated edition of the classic bestseller, Evelyn Tribole and Elyse Resch teach readers how to: Follow the ten principles of Intuitive Eating to achieve a new and trusting relationship with food Fight against diet culture and reject diet mentality forever Find satisfaction in their food choices Exercise kindness toward their feelings, their bodies, and themselves Prevent or heal the wounds of an eating disorder Respect their bodies and make peace with food—at any age, weight, or stage of development Follow body positive feeds for inspiration and validation . . . and more easy-to-follow suggestions that can lead readers to integrate Intuitive Eating into their everyday lives and feel the freedom that comes with trusting their inner wisdom—for life.